Lysinibacillus sphaericus Isolated from Palm Oil Waste Land as Lipase Producer - Sumarsih, Sri; Sofijan Hadi; Fatimah; Rizka Diah Fitri; Gilva Illavi (Bogor Agricultural University, Indonesia, 2024)
In this research, lipolyic bacteria have been isolated from palm oil waste land for the production of lipase. Species of potential lipolytic bacteria were identified based on their morphology and sequences of 16 rRNA gene. Enzymes are produced by growing bacteria in a medium with various vegetable oils and nitrogen sources. The enzyme produced by the bacteria measured its lipolytic activity against the substrate para-nitrophenylpalmitate. The lipolytic bacteria was recognized as Lysinibacillus sphaericus L49a based on morphological and phylogenetic analysis. Mineral media with different vegetable oils as carbon sources, and different nitrogen sources were suitable for growth and production of lipase enzymes of L. sphaericus L49a. Culltivation of L. sphaericus L49a in medium containing ammonium sulfate and olive oil produced lipase with the highest lipolytic activity.